Profili problematici del riconoscimento delle qualifiche professionali nell’Unione europea - Edoardo A. Rossi, Leonardo Guidi (Cultura giuridica e diritto vivente, 2016)
[Problematic issues of the recognition of professional qualifications in the European Union] The recognition of professional qualifications between the EU Member States is an expression of the EU principles of freedom of movement and establishment. Indeed, the abolition of obstacle for nationals of the Member States is essential to provide for the exercise of the right to pursue a profession in a Member State other than the one in which they have obtained their professional qualifications. Nevertheless, the current system of recognition raises problems of conformity and compatibility with the constitutional and European principles.